HUBUNGAN KESEIMBANGAN DENGAN KEMAMPUAN TEKNIK SEPAK SILA DALAM PERMAINAN SEPAK TAKRAW DI CLUB SEPAK TAKRAW PCR PEKANBARU - Jono Jono; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this study is service errors that do not pass through the net, smash out the field, the bait is not good, the reception of the first ball more failed than the opponent's service, the lack of mastery of soccer techniques, less in acceptance of the first ball, body position often lose balance when feeding the ball. The purpose of this research is to find out whether there is a balance relationship with soccer technique skills in the game sepak takraw at Pekanbaru PCR sepak takraw club. The population in this study is all the young players PCR club which amounted to 12 people. A sampling technique was the overall population (total sampling), Instrument performed research is a balance test stork balance stand test which aims to measure the level of balance in a person performing movement.and test soccer skills capabilities aimed at knowing how much ability in performing soccer techniques from the sample used. After that, the data was analyzed to test for normality test at significant level a0,05 lilifors. Based on the research results, it can be concluded as follows.. Based on the results research, it can be concluded as follows. From the results obtained the balance does not have a significant relationship to soccer skills capabilities in club sepak takraw PCR Pekanbaru. where rhitung at significant level α (0,05) = 0.582, means rhitung (0.582)<rtabel (0.602)Keywords: balance, ability of soccer technique sila